Bioactive potential of riparina synthetic analogs: a systematic review (Research, Society and Development, 2021)
Objective: To carry out a systematic review of studies with synthetic analogues of Aniba riparia, riparins A, B, C, D, E and F, in order to highlight the pharmacological potentials already elucidated. Methodology: Three databases were used to select the articles to be included in the Embase, Pubmed and Web of Science review, with the following simplified search strategy (Riparin or Aniba riparia), at the end of the selection, resulting in 10 articles for the elaboration of this work. Results: Publications of studies with synthetic derivatives were identified between the years 2014 to 2021. Most of the researches used riparin A, followed by B, and all were pre-clinical studies. Important pharmacological effects have been reported, such as antibacterial, antifungal, anti-inflammatory, antinociceptive, antitumor, immunomodulatory, antiprotozoal, antiparasitic, anxiolytic and antioxidant activities. Discussion: Studies carried out with synthetic analogues have placed them as possible therapeutic tools, considering the important pharmacological activities already reported. Conclusion: However, considering that the literature already reports six synthetic riparins, the number of articles published aimed at elucidating possible pharmacological activities seems small, even though they are promising candidates for the development of research aimed at discovering new drugs.